Old Testament Theology in Outline. - Zimmerli, Walther (Continuum International Pub. Group, 1983)
During the period that the Old Testament came into being, Israel, from who whose world the documents contained in the Old Testament derive, underwent many changes, especially in its sociological structures. Such changes produce changes in liturgical life, resulting finally in the elimination of a multiplicity of sanctuaries and focusing on Jerusalem. Walther Zimmerli suggests that a presentation of Old Testament theology cannot close its eyes to all this movement and change. This classic study expertly outlines the essential religious structures and tensions of the Old Testament.